Effect of Video-Based Rehabilitation as an Adjunct to Physiotherapy in Post Stroke Patients - Dollar J Brahambhatt1, G Varadharajulu2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objectives: Objective of this study was to evaluate the effects of video-based rehabilitation along with physiotherapy in improving the activities of daily living in stroke patients and evaluating its effects on spasticity. Methodology: There were total 37 subjects, out of which 30 stroke patients were the participants of the study. This was a study to evaluate the effects of video-based rehabilitation along with physiotherapy in stroke patients. Here patients were evaluated on the basis of Modified Ashworth Scale and Modified Barthel Index before the treatment. Patients were showed videos of activities of daily living for 3 minutes every day after their physiotherapy session for 12 weeks and were assessed daily. At the end of the last session the patients were reassessed and re-evaluated on the basis of the same scales. Result: There is a significant change in performing the activities of daily living and spasticity of the patients after 12 weeks of treatment compared to before treatment Conclusion: Activity of daily living can be performed better with the help of videos, and daily physiotherapy sessions, video-based rehabilitation and physiotherapy also has an impact on reducing spasticity in stroke patients.